Employee Performance at the Ratahan Sub-District Office, Southeast Minahasa Regency - Devie S. R. Siwij,; Jeane E. Langkai,; Gloria Adrian, (Technium Social Sciences Journal, 2023)
This study aims to discover, analyze and describe worker overall performance in records collection using commentary, interview and documentation techniques. records analysis via facts reduction, facts Presentation, and Drawing Conclusions. studies used is descriptive qualitative. sources of records used are number one facts and secondary facts. information series the usage of commentary techniques, interviews and documentation. statistics analysis via records reduction, Datsa Presentation, and Drawing Conclusions. The studies vicinity is within the Ratahan Sub-district office, Southeast Minahasa Regency. based on the consequences of the take a look at, it may be concluded that the overall performance of personnel at the Ratahan sub-district workplace is reviewed from 4 assessment signs 1. Service Standards Employee performance is not optimal and effective. 2. Feedback Employee performance is still not up to standard. 3. Facilities and infrastructure Facilities are inadequate, or still not up to standard, in terms of service employees have high discipline. 4. The competence of Service Provider Officers is reviewed after the completion time, there is a guarantee for completion time, but there are several internal and external factors that make the process of making this document hampered, the service process is free of charge.